2002
DOI: 10.1073/pnas.262658999
|View full text |Cite
|
Sign up to set email alerts
|

An epigenetic mouse model for molecular and behavioral neuropathologies related to schizophrenia vulnerability

Abstract: Reelin and glutamic acid decarboxylase (GAD)67 expressed by cortical ␥-aminobutyric acid-ergic interneurons are downregulated in schizophrenia. Because epidemiological studies of schizophrenia fail to support candidate gene haploinsufficiency of Mendelian origin, we hypothesize that epigenetic mechanisms (i.e., cytosine hypermethylation of CpG islands present in the promoter of these genes) may be responsible for this downregulation. Protracted L-methionine (6.6 mmol͞kg for 15 days, twice a day) treatment in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
249
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(266 citation statements)
references
References 37 publications
(48 reference statements)
13
249
0
2
Order By: Relevance
“…10 VPA-induced hyperacetylation of histone proteins has also been shown in mouse brain studies in vivo. 36,37 The requirement of protracted pretreatment for HDAC inhibitors to elicit neuroprotective effects in our studies suggests an involvement of changes in gene expression. VPA has been reported to enhance the expression of cytoprotective proteins such as Bcl-2, 38 GRP (glucose-regulated protein), 39 heat-shock protein 70, 40,41 and brain-derived neurotrophic factor.…”
Section: Discussionmentioning
confidence: 82%
“…10 VPA-induced hyperacetylation of histone proteins has also been shown in mouse brain studies in vivo. 36,37 The requirement of protracted pretreatment for HDAC inhibitors to elicit neuroprotective effects in our studies suggests an involvement of changes in gene expression. VPA has been reported to enhance the expression of cytoprotective proteins such as Bcl-2, 38 GRP (glucose-regulated protein), 39 heat-shock protein 70, 40,41 and brain-derived neurotrophic factor.…”
Section: Discussionmentioning
confidence: 82%
“…Several mechanisms of action have been proposed to explain the actions of MAM-E17 treatment, including a decrease in the levels of reelin and the 67 kDa form of glutamic acid decarboxylase (GAD67), as reported in schizophrenic patients, or by methylation of genes critical for neuronal development and plasticity [158][159][160] . Neuroanatomical findings reported in parallel for the MAM-E17 model and schizophrenic patients include morphological changes in the prefrontal cortex, parahippocampal cortex and hippocampus, reduced size of the medial dorsal thalamus and increased neuron packaging in the frontal lobe 114,[161][162][163][164][165] .…”
Section: Interruption Of Neurogenesismentioning
confidence: 99%
“…Tremolizzo et al 311 investigated whether the Reln rl/ þ mouse model has enhanced susceptibility for epigenetic effects by using a chronic L-methionine dosing regimen to induce hypermethylation in brain. The researchers found that both Reln þ / þ and Reln rl/ þ mice had markedly reduced levels of reelin and GAD67 mRNA levels, as well as alterations in prepulse inhibition of acoustic startle responses, following the protracted exposure to L-methionine.…”
Section: Epigenetic Regulation and Autismmentioning
confidence: 99%